2021
DOI: 10.3389/fmed.2021.667525
|View full text |Cite
|
Sign up to set email alerts
|

FABP5, a Novel Immune-Related mRNA Prognostic Marker and a Target of Immunotherapy for Multiple Myeloma

Abstract: Objective: Multiple myeloma is an incurable hematological malignancy. It is imperative to identify immune markers for early diagnosis and therapy. Here, this study analyzed immune-related mRNAs and assessed their prognostic value and therapeutic potential.Methods: Abnormally expressed immune-related mRNAs were screened between multiple myeloma and normal bone marrow specimens in the GSE47552 and GSE6477 datasets. Their biological functions were then explored. Survival analysis was presented for assessing progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In addition to its upregulation and functions in tumor cells, FABP5 is also found to be dysregulated in multiple immune cell types and can serve as a novel immune-related prognostic marker and a target of immunotherapy[ 23 ]. FABP5 was reported to regulate mitochondrial integrity and functions as cell-intrinsic checkpoint for Treg suppressive function in tumor microenvironment[ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its upregulation and functions in tumor cells, FABP5 is also found to be dysregulated in multiple immune cell types and can serve as a novel immune-related prognostic marker and a target of immunotherapy[ 23 ]. FABP5 was reported to regulate mitochondrial integrity and functions as cell-intrinsic checkpoint for Treg suppressive function in tumor microenvironment[ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that FABP5 can reprogram lipid metabolism and promote progression and metastasis in tumors ( 74 76 ). Furthermore, FABP5 has been shown to act as a critical regulator of immune cells in microenvironments via lipid metabolism, including the protection of tissue-resident memory T cells ( 77 ), the induction of suppressive T regulatory cells ( 67 , 78 ), the maintenance of T lymphocyte homeostasis ( 79 ), the production of tolerogenic plasmacytoid dendritic cells ( 78 ), and macrophage polarization, and has also been identified as a prognostic immune-metabolic marker ( 80 , 81 ). Similarly, we identified the immunomodulatory effect of FABP5 during the differentiation of decidual PMN-MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins that comprise the fatty acid binding protein family, known as FABPs, have recently been implicated as prognostic markers identifying more aggressive myeloma cells, as we reported earlier this year in eLife [ 1 ]. The FABPs hold promise as new therapeutic targets in multiple myeloma (MM), as described by our laboratory, and supported by in silico analyses [ 2 ] and other data [ 3 , 4 ]. In multiple datasets, (including GSE4452, GSE4204, GSE132604, GSE4452, GSE9782, and the MMRF’s CoMMpass dataset) progression free survival and overall survival were worse for patients with high tumor cell expression of FABP5 .…”
mentioning
confidence: 83%
“…Jia et al also found differences in immune-related mRNA expression between MM patient bone marrow (BM) and normal BM, and observed that FABP5 expression in MM cells correlates with immune cell changes in the tumor microenvironment [ 2 ]. These data suggest that FABP5 expression in MM cells may also influence tumor progression by affecting the infiltrating BM immune cells.…”
mentioning
confidence: 99%